Ecomorphic organisation of the mesopedobionts community as the basis of the anthropogenic soils zoological diagnostic - Андрусевич, К. В.; Жуков, О. В.; Кунах, О. М. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
The connection between soil mesofauna community ecomorphic structures of pedozem and some characteristics of this soil and the vegetative cover expressed in terms of phytoindicator scales and plant ecomorphes has been established by means of RLQ-analysis. Within studied polygon, the community of soil mesofauna has been found to be distributed not in a random way. This distribution is determined by edafic properties and can be interpreted by means of the analysis of ecomorphes functional importance. The established dependences of ecomorphic structures of soil mesofauna on pedozem edafic properties may be the basis of application of ecomorphic approaches for the zoological diagnostics of anthropogenous soils.